PREDICTION OF HYPOECHOIC LESIONS ON ULTRASOUND OF PROSTATE CANCER BASED ON PSA INTERVAL AND GLEASON GROUP - Ivan Mangunsong, Albert; Pramod, Sawkar Vijay; Safriadi, Ferry; Hernowo, Bethy S (Indonesian Journal of Urology, 2021)
Objective: To evaluate hypoechoic lesion in transrectal ultrasonography of prostate (TRUS-P) predictive value on prostate cancer based on PSA Interval and Gleason Group. Material & Methods: An observational analytic study with a cross-sectional design take place from January 2015 to December 2018 analyzing patients who had undergone TRUS-P Biopsy at Hasan Sadikin Hospital. Patients are divided into several subgroups according to different PSA levels. A p-value < 0.05 was considered statistically significant. PPV, NPV, and Youden’s index were all indexes reflecting the performance of a diagnostic test. Results: There were 35 cases (49.3%) with a visible hypoechoic lesion in TRUS and 36 cases (41.7%) without a visible hypoechoic lesion. In our study, 23.9% of the patients with hypoechoic lesions were diagnosed with prostate cancer on TRUSP-Biopsy. The results of the analysis with Youden’s index show that PSA at intervals of 10-20 is the best predictor of diagnostic values. Then we analyzed the overall detection rate based on PSA interval. Patients with PSA > 20 ng/ml, hypoechoic lesions were significantly associated with Gleason Group. Conclusion: We concluded in our study that the hypoechoic lesion in transurethral ultrasonography of prostate could improve the predictive efficacy for diagnosing prostate cancer.